2012
DOI: 10.1007/s00417-012-2226-y
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes and complications following posterior iris-claw aphakic intraocular lens implantation combined with penetrating keratoplasty

Abstract: Retropupillar iris-claw IOL during penetrating keratoplasty provides good visual outcomes with a favorable complication rate, and can be used for a wide range of indications in eyes without adequate capsule support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 22 publications
4
19
0
2
Order By: Relevance
“…Retropupillary implantation of a similar Verisyse ® iris claw lens after vitrectomy has also been reported 1821. Although implanting the iris claw lens above the iris for aphakic eyes may decrease the endothelial cell count, in most studies using the retropupillary fixation technique, a significant effect was not found on the endothelial cell count, as in the present study 22,23…”
Section: Discussionsupporting
confidence: 69%
“…Retropupillary implantation of a similar Verisyse ® iris claw lens after vitrectomy has also been reported 1821. Although implanting the iris claw lens above the iris for aphakic eyes may decrease the endothelial cell count, in most studies using the retropupillary fixation technique, a significant effect was not found on the endothelial cell count, as in the present study 22,23…”
Section: Discussionsupporting
confidence: 69%
“…Several studies have indicated favourable visual outcomes and a low incidence of intraoperative and postoperative complications with aphakic iris-claw IOLs 5 6 14 16 22–24. These implants used to be positioned in the anterior chamber only but are more and more inserted retropupillary in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Several case series have demonstrated its safety and good visual results 4,68. The technique is simple, less time consuming, and has a lower postoperative complication rate than other techniques 911.…”
Section: Discussionmentioning
confidence: 94%